The effects of microfibers on electrical characteristics of zinc oxide thin film transistor - Alahmed, Zeyad A.; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
The high mobility n-type thin film transistor based on sol-gel processed zinc oxide (ZnO) was fabricated. The ZnO thin film was prepared by spin coating the precursor solution on a SiO2 dielectric layer. AFM results indicate that the ZnO film is formed from the microfibers. The solution-processed ZnO TFT was found to exhibit a high mobility of 0.47 cm(2)/V.s. This indicates that the microfiber ZnO film has a important effect to fabricate a high mobility ZnO thin film transistor. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Thin film transistor; Solution process; Field effect mobility